Tropism, Cytotoxicity, and Inflammatory Properties of Two Envelope Genes of Murine Leukemia Virus Type-Endogenous Retroviruses of C57BL/6J Mice - Young-Kwan Lee; Alex Chew; David G. Greenhalgh; Kiho Cho (Mediators of Inflammation)
Envelope (env) proteins of certain endogenous retroviruses (ERVs) participate in various pathophysiological processes. In this study, we characterized pathophysiologic properties of two murine leukemia virus-type ERV (MuLV-ERV) env genes cloned from the ovary of C57BL/6J mice. The two env genes (named ENVOV1 and ENVOV2), with 1,926\,bp coding region, originated from two MuLV-ERV loci on chromosomes 8 and 18, respectively. ENVOV1 and ENVOV2 were ~75 kDa and predominantly expressed on the cell membrane. They were capable of producing pseudotype murine leukemia virus virions. Tropism trait and infectivity of ENVOV2 were similar to the polytropic env; however, ENVOV1 had very low level of infectivity. Overexpression of ENVOV2, but not ENVOV1, exerted cytotoxic effects and induced expression of COX-2, IL-1β, IL-6, and iNOS. These findings suggest that the ENVOV1 and ENVOV2 are capable of serving as an env protein for virion assembly, and they exert differential cytotoxicity and modulation of inflammatory mediators.